Imagens da África, dos africanos e seus descendentes em coleções de didáticos de história aprovadas no PNLD de 2004 - Boulos Júnior, Alfredo (2008)
Focusing on school images, on their multiple relationships with text and the typographic configuration, this work has intended to cooperate in facing a Bittencourt (1993) identified demand: the exiguity among us of studies on iconography which concentrate in their own image. Aware of this gap, we have investigated the representations of Africa, of the africans and their descendants in three Elementary School collections, approved and recommended by MEC in PNLD of 2004. Firstly we focused on the images themselves and, only secondarily, on the texts written about them and on the graphical aspects. As concerns the text, we have priviledged the captions, images titles and side comments about them. We endeavoured to quantify them in the studied collections, scrutinize their functions and their distribution throughout the units and lessons; their distribution per type seeking to extract our analysis from there. Upon developing our research we seeked to dimension the role of the Black Movement and the State in the changes occurred in the school books assessment process, as well as the repositioning of didactic material producers when facing the new demands of the mentioned social actors. We have dedicated to reading such repositioning in the imagetic, textual and typographic devices used to propose to the reading of State assessed and recommended collections. That is, we have seeked to understand the way of representing Africa, the africans and their descendants from the materiality of these collections. The results obtained in the research suggest shy changes in that way of representation; the permanences, in turn, are many; one of them is the fact that afrodescendants are predominantly represented and described in the past; it has also been observed that, when represented in the present, the images are, most times, stiff posing pictures, with no mention whatsoever as to time and place. Following the tracks opened by Cultural History we used as a theoretical support the concepts of social representation and representations fights, as formulated by Roger Chartier and the strategical and tactical ones, as conceived by Michel de Certeau